Building Multicultural Understanding Through Student Competence: A Conceptual Framework - Nizam, Awang Khairul; Khairan, Mirzaq; Corliss, Tayven; Alwyn, Seren (Universitas Muhammadiyah Surakarta, 2025)
Increased globalization, migration, and academic mobility have brought significant cultural diversity into education, particularly in the health sciences. This diversity presents both opportunities and challenges ranging from enriched learning environments to communication barriers and stereotyping. However, prior studies on intercultural competence among students often remain fragmented, context-specific, and lack a unifying conceptual framework. This study addresses that gap by conducting a bibliometric analysis of 585 peer-reviewed articles published between 2015 and 2025, retrieved from the Scopus database, to map global research trends related to cultural diversity and student competence. Utilizing the bibliometrix package in R, the study identifies key themes, leading authors, collaborative networks, and keyword clusters. The analysis reveals a strong focus on cultural competence, language, cultural anthropology, and institutional management, especially within nursing and medical education. The study then develops an evidence-based conceptual framework comprising student competence as the dependent variable; cultural exposure, language proficiency, and cultural knowledge as independent variables; cultural competence as a mediating factor; and institutional support and bias as potential moderators. The findings offer both theoretical and practical contributions: advancing the integration of interdisciplinary theories such as Contact Hypothesis and Transformative Learning Theory into intercultural education research, while also guiding future empirical studies. This framework provides a foundation for designing culturally responsive curricula and institutional strategies in increasingly diverse educational settings